Urinary transforming growth factor-β1 in children with obstructive uropathy - Zieg, Jakub; Blahova, Kveta; Seeman, Tomas; Bronsky, Jiri; Dvorakova, Hana; Pechova, Marta; Janda, Jan; Matousovic, Karel (Nephrology (Carlton, Vic.), 2011)
AIM: Obstructive uropathies (OU) in childhood constitute one of the major causes of chronic renal insufficiency. Transforming growth factor-β1 (TGF-β1) is considered to be the major fibrogenic growth factor. The aim of the present study was to investigate urinary TGF-β1 levels in children with obstructive and non-obstructive uropathies (NOU). METHODS: This study involved 19 children with OU, 11 children with non-obstructive hydronephrosis and 21 healthy children. Urinary TGF-β1, proteinuria, microalbuminuria and urinary α1-microglobulin were measured, and renal function was assessed. The results were statistically analyzed. RESULTS: Mean urinary TGF-β1 concentrations in patients with OU were significantly higher than those with NOU (4.14 ± 0.67 creatinine vs 1.80 ± 0.24 pg/mmol creatinine, P < 0.05) and healthy controls (1.66 ± 0.28 pg/mmol creatinine, P < 0.05). Positive correlations of urinary TGF-β1 concentrations with proteinuria (r = 0.87, P < 0.0001) and urinary α1-microglobulin (r = 0.82, P = 0.0002) were found in patients with OU. CONCLUSION: Children with OU have higher urinary TGF-β1 than children with NOU. Urinary TGF-β1 may be a useful non-invasive tool for the differential diagnosis between OU and NOU in children. A positive correlation of TGF-β1 with markers of renal tissue damage in patients with OU was found.
Keywords: biologické markery; Alpha-Globulins; Česká republika; obstrukce močovodu; Transforming Growth Factor beta1; Child, Preschool; analýza rozptylu; předškolní dítě; Hydronephrosis; lidé; Czech Republic; transformující růstový faktor beta1; albuminurie; Analysis of Variance; studie případů a kontrol; Up-Regulation; kojenec; Female; chronická renální insuficience; Predictive Value of Tests; průřezové studie; hodnoty glomerulární filtrace; kreatinin; upregulace; Biomarkers; Male; ženské pohlaví; Case-Control Studies; Cross-Sectional Studies; Humans; mužské pohlaví; ledviny; Urethral Obstruction; prediktivní hodnota testů; Infant; Creatinine; alfa-globuliny; Glomerular Filtration Rate; Kidney; Albuminuria; Renal Insufficiency, Chronic; Ureteral Obstruction; hydronefróza; obstrukce močové trubice